Fabrication of an (α-Mn2O3:Co)-decorated CNT highly sensitive screen printed electrode for the optimization and electrochemical determination of cyclobenzaprine hydrochloride using response surface methodology. Issue 42 (1st July 2020) - Abdel-Raoof, Ahmed M.; Osman, Ayman O. E.; El-Desouky, Ebrahim A.; Abdel-Fattah, Ashraf; Abdul-Kareem, Rady F.; Elgazzar, Elsayed
Abstract : A new chemically optimized screen-printed electrode modified with a cobalt-doped α-Mn2 O3 nanostructure on carbon nanotube paste (α-Mn2 O3 :Co@CNTs) has been constructed for the recognition of cyclobenzaprine hydrochloride. Abstract : A new chemically optimized screen-printed electrode modified with a cobalt-doped α-Mn2 O3 nanostructure on carbon nanotube paste (α-Mn2 O3 :Co@CNTs) has been constructed for the recognition of cyclobenzaprine hydrochloride. The prepared paste is based on the incorporation of oxide ion conductors, such as the α-Mn2 O3 nanostructure with cobalt and ion pairs (tetraphenyl borate coupled with the drug), as electroactive species in the screen-printed electrode to increase the sensor surface area and decrease electrical resistance. The central composite design is a useful methodology for the estimation and modeling of the exact optimum parameters specifically designed for this process. This is a good way to graphically clarify the relationship between various experimental variables and the slope response. The proposed sensor, α-Mn2 O3 :Co@CNTs, possesses very good sensitivity and the ability to recognize the drug over the concentration range of 1 × 10 −6 to 1 × 10 −2 mol L −1 at 25 ± °C with a detection limit of 2.84 × 10 −7 mol L −1 . It exhibits a reproducible potential and stable linear response for six months at a Nernstian slope of 58.96 ± 0.76 mV per decade. The proposed electrode approach has been successfully applied in the direct determination of the drug in its pure and dosage forms.